Of words and deeds: Latin American declaratory regionalism, 1994–2014*. Issue 2 (4th March 2017) - Jenne, Nicole; Schenoni, Luis Leandro; Urdinez, Francisco
Abstract: The idea of an integrated Latin American region goes back to the early post-independence period, and yet, in substance, Latin American regionalism has remained far behind its stated aims. The perceived implementation gap has raised the question why policymakers continued to talk about something they appeared to avoid in practice. This article contributes to the debate on Latin America's integration gap by exploring the phenomenon of declaratory regionalism - the practice of referring to the region and its institutions in political speeches. Based on quantitative text analysis of the speeches presidents delivered annually at the UN's General Assembly between 1994 and 2014, we show that this practice has not been uniform. Presidents distinguish between different forms of regionalism, integration and cooperation, and frame the geographical region they refer to accordingly. In motivating presidents to speak about integration as opposed to cooperation, ideology and democratic performance stand out as crucial factors.